The test of time: A longitudinal study of parasocial relationships with social media influencers - Azhar, Kaukab Abid; Wel, Che Aniza Che; Hamid, Siti Ngayesah Ab (International Journal of Innovative Research and Scientific Studies, 2025)
This study examines the long-term sustainability of parasocial relationships with social media influencers and their influence on brand attitudes and purchase intentions. While prior research has explored the immediate effects of influencer marketing, little is known about how these relationships evolve over time. Grounded in social exchange theory, this longitudinal panel study tracks changes in parasocial relationships over a one-year period. Data were collected from 223 participants in Pakistan through an e-commerce platform. Multiple regression analyses and paired sample t-tests were conducted to assess shifts in source attractiveness—comprising physical attractiveness, likability, and perceived similarity—and their impact on consumer attitudes and behavior. The results reveal a significant decline in the strength of parasocial relationships over time, driven primarily by decreasing likability and perceived similarity, while physical attractiveness remained relatively stable. This decline corresponded with a reduced positive influence on brand attitudes and purchase intentions. The weakening of parasocial relationships suggests that influencer marketing effects may not be as enduring as previously assumed. These findings highlight the need for brands to adopt strategies that sustain audience engagement beyond initial attraction. Brands must recognize that an influencer’s appeal is not static and that long-term brand advocacy requires active relationship maintenance. Additionally, brands should develop progressive endorsement strategies, where influencers are gradually integrated into different stages of the consumer journey, rather than being used for one-off promotions.